Strategic Planning of Work Training Center Information System Using TOGAF ADM and ITIL - M. Norman Fither; Aji Supriyanto (Green Publisher Indonesia, 2024)
This study aims to develop an implementation model of TO-GAF and ITIL frameworks in enterprise architecture (EA) for the Technical Implementation Unit (UPTD) of the Tegal Re-gency Vocational Training Center (BLK) and determine the improvement of services provided by BLK after the develop-ment of enterprise architecture. This type of research is a case study research where data collection is done by direct observation or observation, interviews and surveys using questionnaires. The population in this study were employees and students of BLK Tegal Regency, totaling 100 people. While the sample was 15 people. TOGAF ADM is used to un-derstand the strategic planning process systematically, from problem identification to the development of measurable solutions. Analysis and design of enterprise architecture is prelimenary phase, requirement management, architecture vision, business architecture, information systems architecture and opportunities and solutions. While the ITIL approach in addition to providing practical guidance in managing BLK IT services, ITIL is also used to test the level of maturity of the system against the blueprint produced so that a tested sys-tem design is obtained. The results of the maturity level of the service operation domain system are at level 4 with a value of 3.94 and have not yet reached level 5 which means that some activities have not been fully carried out to the maximum. To achieve the expected maturity process, management must always supervise every decision making in accordance with existing procedures.